2014
DOI: 10.1128/aem.01737-14
|View full text |Cite
|
Sign up to set email alerts
|

Bdellovibrio and Like Organisms Enhanced Growth and Survival of Penaeus monodon and Altered Bacterial Community Structures in Its Rearing Water

Abstract: bIn this study, a 96-h laboratory reduction test was conducted with strain BDHSH06 (GenBank accession no. EF011103) as the test strain for Bdellovibrio and like organisms (BALOs) and 20 susceptible marine bacterial strains forming microcosms as the targets. The results showed that BDHSH06 reduced the levels of approximately 50% of prey bacterial strains within 96 h in the seawater microcosms. An 85-day black tiger shrimp (Penaeus monodon) rearing experiment was performed. The shrimp survival rate, body length,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…The fact that the experimental results concerned native predators in NWs adds relevance to the findings. Other investigators using different experimental models have also reported a reduction of prey bacteria by Halobacteriovorax and the potential of the predators to affect the mortality of susceptible bacterial populations in aquatic systems (Richards et al, 2012;Li et al, 2014;Wen et al, 2014). Richards et al (2012) used several strains of V. parahaemolyticus and a strain of V. vulnificus as amendments to a natural seawater sample and observed a decline in their numbers along with an increase in Halobacteriovorax as we observed in the experiments described in this report.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The fact that the experimental results concerned native predators in NWs adds relevance to the findings. Other investigators using different experimental models have also reported a reduction of prey bacteria by Halobacteriovorax and the potential of the predators to affect the mortality of susceptible bacterial populations in aquatic systems (Richards et al, 2012;Li et al, 2014;Wen et al, 2014). Richards et al (2012) used several strains of V. parahaemolyticus and a strain of V. vulnificus as amendments to a natural seawater sample and observed a decline in their numbers along with an increase in Halobacteriovorax as we observed in the experiments described in this report.…”
Section: Discussionsupporting
confidence: 68%
“…The fact that Halobacteriovorax are also abundant in the surface microlayer (Williams, 1987) suggests that they prey on the large numbers of bacteria present. Although high concentrations of prey were used in this study, it should be noted that BALOs are typically capable of reducing prey concentrations via population dynamics similar to those shown in Figures 2 and 3 at prey concentrations as low as of 1 × 10 4 ml -1 , albeit over a longer time period (Ahmed, 2007;Richards et al, 2012;Li et al, 2014;Wen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One group of Bdellovibrionales, the marine Halobacteriovorax, are broadly distributed in marine waters across temperature, salinity and pH gradients (Pineiro et al, 2007). Halobacteriovorax predation represents a regulatory mechanism that can alter the structure of bacterial communities (Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Considering these factors, the use of probiotics or beneficial bacteria to control pathogens is increasingly viewed as an alternative to antibiotics and vaccines (Balcazar et al ; Kim et al ; Mirbakhsh et al ; Chen et al ). The use of probiotics in aquaculture has originated in human and animals since 1989 (Fuller ) and became popular thereafter (Wang et al ; Selvin and Ninawe ; Villamil et al ; Khanitta and Tipparat ; Wu et al ; Daga' et al ; Pérez‐Sánchez et al ; Li et al ).…”
mentioning
confidence: 99%